Online ordering book system: A case study in Malaysia higher institute - Othman, Zainab; Hasnan, Mazliana; Hasnan, Norlena (2014)
This paper aims to present an e-service project findings conducted in one of the Malaysia Higher Education Institute.The objective of the project is to create a prototype showing the functionalities of Online Ordering Book System. The methodology used was Object Oriented approach where it involved three main phases, which are defining requirements, analyzing requirement and validating functionalities.There are several diagrams involved to show the functionalities of the system which are: use case diagram, use case specification, class diagram, sequence diagram, collaboration diagram, activity diagram and the list of requirement.This prototype provides a guideline in developing a real system of Online Ordering Book based on user’s perspective, particularly in the perspective of academic staff of University Teknologi Mara, Melaka.